2018
DOI: 10.1038/s41598-018-23140-9
|View full text |Cite
|
Sign up to set email alerts
|

Priming the body to receive the therapeutic agent to redefine treatment benefit/risk profile

Abstract: Many therapeutic agents offer a low useful dose (dose responsible for efficacy)/useless dose (dose eliminated or responsible for toxicity) ratio, mainly due to the fact that therapeutic agents must ensure in one single object all the functions required to deliver the treatment, which leads to compromises in their physico-chemical design. Here we introduce the concept of priming the body to receive the treatment by uncorrelating these functions into two distinct objects sequentially administered: a nanoprimer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…Co-delivery of appropriate materials with nanomedicines is another approach. For example, the nano-sized inhibitors of hepatic cytochrome P450 3A4 (CYP3A4) serve as a priming agent to block hepatic metabolism specifically following treatment with nanomedicine, which increases the drug bioavailability and prolongs the survival of the xenograft mice 36,37 . Here, we have provided a novel strategy by using an FDA-approved nutritional supplement, Intralipid, to enhance the drug bioavailability ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Co-delivery of appropriate materials with nanomedicines is another approach. For example, the nano-sized inhibitors of hepatic cytochrome P450 3A4 (CYP3A4) serve as a priming agent to block hepatic metabolism specifically following treatment with nanomedicine, which increases the drug bioavailability and prolongs the survival of the xenograft mice 36,37 . Here, we have provided a novel strategy by using an FDA-approved nutritional supplement, Intralipid, to enhance the drug bioavailability ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, a major challenge to conventional systemic drug delivery is the non-specific uptake of nanomedicines by the reticuloendothelial system (RES), which inhibits payload delivery and imparts toxicity within RES-associated organs, such as the liver, spleen, and kidney (32). In response, there has been a focus on developing nanoprimers that can prepare a patient's body for the subsequent administration of nanomedicines in a manner that will reduce the therapy's risk profile (33). In a recent study, it was demonstrated that the intravenous administration of intralipids one hour prior to therapy was shown to decrease RES uptake, while increasing the nanomedicine's bioavailability (32).…”
Section: Organic Nanocarriersmentioning
confidence: 99%
“…Advantageously, it is not required that modifications be applied to the payload or its carrier in order to confer this synergism, which makes it translatable to other BNT-based therapies (32). Another similar study utilized a non-toxic liposomal nanoprimer that presented low levels of hepatic accumulation and increased the subsequently administered nanomedicine's systemic bioavailability (33). It was found that by loading cytochrome inhibitor within the nanoprimer, the efficiency of docetaxel treatment significantly increased (33).…”
Section: Organic Nanocarriersmentioning
confidence: 99%
See 2 more Smart Citations